Identification of a ferroptosis-related long noncoding RNA signature with a prognostic value in adrenocortical carcinoma - Wang, Weixi; Chang, Guilin; Zhuo, Ran; Ye, Cong (Frontiers in Genetics, 2022)
Background: Adrenocortical carcinoma (ACC) is an uncommon endocrine malignancy associated with poor clinical outcome. As a novel form of cell death, ferroptosis is reliant on the accumulation of iron and reactive oxygen species, and is involved in the pathogenesis of various tumors, including ACC. Our study aimed to identify and characterize the prognostic ferroptosis-related lncRNA signature (FerRLSig) in ACC. Methods: A regulatory network of ferroptosis-related lncRNAs (FerRLs) and mRNAs was constructed based on the Cancer Genome Atlas (TCGA). Univariate and multivariate Cox regression assays were performed to construct the FerRLSig. Results: Twenty-four FerRLs were identified in the prognostic model, and the high-risk FerRLSig was related to worse overall survival (OS) in ACC [hazard ratio (HR): 1.936 (1.484-2.526), P < 0.001]. The area under the curve (AUC) value of the FerRLSig was 0.936 according to the receiver operating characteristic (ROC) analyses, superior to other traditional clinicopathological features, further supported the utility in prognosis prediction of ACC. We further established a prognostic nomogram combining clinical factors with the FerRLSig, which showed favorable efficacy for survival prediction. Next, gene set enrichment analysis (GSEA) revealed that gene sets were involved in many immune regulatory biological processes related to malignancies. T cell function of type II INF response as well as the immune checkpoints including CD40, CD276, IDO2, NRP1 and CD80, were expressed with significant difference between the low- and high-risk groups. Conclusions: This study offered new insights in the pathogenesis of ACC. The novel FerRLSig could be useful in predicting survival and may provide information of immunological research and treatment for ACC patients.